There is no planet B - Panayides, Angelos (My University, 2023)
A. Social or Political Posters (commissioned or non-commissioned work) In the current category we welcome posters that incorporate social or political messages as major aims to target specific audiences in different contexts. Within this framework we accept posters that explore a wide range of issues and pursue to have an influence on civilians’ lives as well as improve local or international politics.
Keywords: poster, trienale, exhibition, catalogue, graphic design